Study of an organically modified clay: Selective adsorption of heavy metal ions and voltammetric determination of mercury(II) - Dias, N. L.; do Carmo, D. R. (Elsevier B.V., 2006)
In this work, a hydrophilic clay, Na-montmorillonite from Wyoming, USA, was rendered organophilic by exchanging the inorganic interlayer cations for hexaclecyltrimethylammonium ions (HDTA), with the formulae of [(CH3)(3)N(C16H33)](+) ion. Based on fact that organo-clay has high affinities for non-ionic organic molecules, 1,3,4-thiadiazole-2,5-dithiol was loaded oil the HDTA-montmorillonite surface, resulting in the 1,3,4-thiadiazole-2,5-dithiol-HDTA-montmorillonite complex (TDD-organo-clay).The following properties of TDD-organo-clay are discussed: selective adsorption of heavy metal ions measured by batch and chromatographic column techniques, and utilization as preconcentration agent in a chemically modified carbon paste electrode (CMCPE) for determination of mercury(II).The main point of this paper is the construction of a selective sensor, a carbon paste electrode modified with TDD-organo-clay, its properties and its application to the determination of mercury(II) ions, as this element belongs to the most toxic metals. The chemical selectivity of this functional group and the selectivity of voltammetry were combined for preconcentration and determination. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: adsorption; organo-clay; carbon paste electrodes; voltammetry; mercury; preconcentration